DEVELOPING STORIES AS MINDFUL LEARNING MATERIALS FOR INDONESIAN EFL LEARNERS - Aldila Ihsania Mufidah; Irene Nany Kusumawardani (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2023)
In the era where fictional works are popular with teenagers while there are still challenges in understanding English, the researchers conducted a study to develop stories with the title “Berteman itu Sulit”. One of the challenges is the lack of varied learning material in grammar learning. The researchers propose to develop an English material based on the students’ own life context, that is mental health, to make the post-pandemic learning process interesting. The short stories are used as English mindful material with 5 tenses included; simple present tense, present continuous tense, simple past tense, past continuous tense, and present perfect tense. In developing short stories, the researchers went through 4 steps; 1) story development; 2) validation; 3) publication; 4) trying out 10 EFL students from random schools. With a total of 13 parts, the stories are being published on Wattpad platform, the most popular fiction reading site in the post-pandemic era. There are three things to be underlined as the result; 1) the content for grammar material is adequate; 2) the learning material is validated as mindful and suitable for students to read; 3) the try-out questionnaire showed positive results of EFL learners’ perspective to the material.